How Is the Neural Response to the Design of Experience Goods Related to Personalized Preference? An Implicit View - Ma, Yongbin; Jin, Jia; Yu, Wenjun; Zhang, Wuke; Xu, Zhijiang; Ma, Qingguo (Frontiers in Neuroscience, 2018)
Understanding the process by which consumers evaluate the designs of experience goods is critical for firms designing and delivering experience products. As the implicit process involved in this evaluation, and given the possible social desirability bias inherent to traditional methods of product design evaluation in certain conditions, neuroscientific methods are preferred to gain insight into the neural basis of consumers’ evaluation of experience good designs. We here used event-related potentials (ERPs) and a revised go/no-go paradigm to investigate consumers’ neural responses to experience good designs. Personalized product designs and neutral landscape pictures were randomly presented to 20 student participants; they were asked to view these product designs without making any decisions. The paired t-test and repeated-measures analysis of correlation showed that the P200 and late positive potential (LPP) elicited by the most-preferred experience good designs were significantly higher than that elicited by least-preferred designs, and the two ERP components were positively correlated with the personalized rating scores. Thus, P200 and LPP might be the early and late indices of consumers’ evaluation of experience good designs, respectively, and may facilitate an understanding of the temporal course of this evaluation. Furthermore, these two ERP components can be used to identify consumers’ preferences toward experience good designs. In addition, given the use of personalized experimental stimuli, these findings may help to explain why customized products are preferred by consumers.